Shooting Simulation Based On Computer Vision Using Programming Language Phyton and Borland Delphi 7 - Sugeng Wahyudiono; Tri Yusnanto; Kanafi (Journal of Intelligent Decision Support System (IDSS), 2022)
The purpose of this research is to be able to Design and Build a Scenario Video Shooting Simulation Based on Computer Vision Programming at the Military Academy using Python and Borland Delphi 7 Programming Languages to be used as a means of shooting practice by cadets. The research methodology employed uses the Waterfall method with research stages: Communication, Planning, Modeling, Construction, and Deployment. And the data collection method in making this Shooting Simulation uses Interviews, Observation, and Documentation. The design used in this study is UML (Unified Modeling Language) modeling. A system designer must follow the existing rules when he uses UML modeling. System testing in this study uses Black Box Testing. The result of this research is to produce an application that is easy to use in shooting training at the Magelang Military Academy.